Spatial and trophic structure drive ecomorphological patterns of fish assemblages in oligotrophic headwater streams of northwestern Amazonia - Francisco Javier Luque; Gabriel J. Colorado Z. (Neotropical Ichthyology)
Abstract This study evaluated the ecomorphological patterns of fish assemblages in oligotrophic headwater streams of northwestern Amazonia. Our aims were: 1) identify correlations between morphological variables of fish species and habitat use, trophic structure and distance to the main river; 2) examine ecomorphological patterns that reflect ecological aspects of locomotion, habitat use and trophic ecology. A total of 34 species were analyzed using 27 ecomorphological indices to test if they were related to fish assemblage. Significant correlations were found between anatomical traits and trophic guilds and habitat use regardless of phylogenetic relationships. Two trends were identified in the ecomorphological space. First, nektonic insectivores-piscivores with lateral compressed bodies, large eyes, superior-terminal mouth without barbels and larger anal fins were associated to species with continuous swimming, and the use of vision to capture prey. Second, benthic periphytivores-invertivores with depressed bodies, small eyes, ventral or inferior mouth with presence of barbels, and developed pectoral fins were related to species that exploit streams substrate. This study shows that fish assemblages in the oligotrophic headwater streams are ecomorphologically structured by trophic guilds and habitat use. These findings highlight the use of ecomorphology as a tool to predict ecological patterns in these streams.